The Value of Working Conditions in the United States and Implications for the Structure of Wages - Nicole Maestas; Kathleen Mullen; David Powell; Till von Wachter; Jeffrey Wenger (Institute of Labor Economics (IZA), 2018)
This paper documents variation in working conditions among workers in the United States, presents new estimates of how workers value these conditions, and assesses the impact of working conditions on estimates of the wage structure and inequality. We use evidence from a series of stated preference experiments to estimate workers' willingness-to-pay for a broad set of job characteristics, which we validate with actual job choices. We find that working conditions vary substantially across workers, play a significant role in job choice decisions, and are central components of the compensation received by workers. Preferences vary by demographic groups and throughout the wage distribution. We find that accounting for differences in preferences for working conditions often exacerbates wage differentials by race, age, and education, and intensifies measures of wage inequality.
Keywords: J13; 330; working conditions; wages; compensating differentials; stated preferences